MHD fluid flow and heat transfer due to a stretching rotating disk - Turkyilmazoglu, Mustafa (International journal of thermal sciences, 2012)
The steady MHD laminar flow of an electrically conducting fluid on a radially stretchable rotating disk in the presence of a uniform vertical magnetic field is the subject of the present paper. The problem is an extension of the well-known von Karman viscous pump problem to the configuration with a stretchable disk with or without rotation first imposed in [1]. The governing equations of motion are reduced to a set of nonlinear differential equations by means of conventional similarity transformations. Energy equation accounts for the viscous dissipation and Joule heating terms. Employing a highly accurate spectral numerical integration scheme, the effects of a rotation parameter based on the wall stretching and angular velocity are examined. The quantities of particular physical interest, such as the torque, the wall shear stresses, the vertical suction velocity and the rate of heat transfer are calculated and discussed. ► Increase of the rotation parameter dramatically increases the near disk velocities. ► The presence of magnetic field acts to reduce the velocity of fluid particles. ► As the rotation parameter grows, all the physical quantities increase. ► Addition of the Joule heating enhances the rate of heat transfer. ► Radial stretching of the disk can overcome the wall heating.